The virtual hearings in criminal proceedings during the national state of emergency - Limaylla Torres, Abraham de Jesús (2021)
In the accusatory criminal process, the trial is based on principles of contradiction, publicity, immediacy, orality, unity, concentration, among others, which are indispensable for its application in the criminal process, especially in the oral trial, although some principles are exceptionally limited by the type of crime being investigated or tried, as occurs in crimes of sexual violation, since the hearings are not public. This limitation is presented during the health emergency by COVID-19, since the hearings are conducted virtually.